Apoptosis-associated uncoupling of bone formation and resorption in osteomyelitis - Marriott, Ian (Frontiers in Cellular and Infection Microbiology, 2013)
The mechanisms underlying the destruction of bone tissue in osteomyelitis are only now being elucidated. While some of the tissue damage associated with osteomyelitis likely results from the direct actions of bacteria and infiltrating leukocytes, perhaps exacerbated by bacterial manipulation of leukocyte survival pathways, infection-induced bone loss predominantly results from an uncoupling of the activities of osteoblasts and osteoclasts. Bacteria or their products can directly increase osteoclast formation and activity, and the inflammatory milieu at sites of infection can further promote bone resorption. In addition, osteoclast activity is critically regulated by osteoblasts that can respond to bacterial pathogens and foster both inflammation and osteoclastogenesis. Importantly, bone loss during osteomyelitis is also brought about by a decline in new bone deposition due to decreased bone matrix synthesis and by increased rates of osteoblast apoptosis. Extracellular bacterial components may be sufficient to reduce osteoblast viability, but the causative agents of osteomyelitis are also capable of inducing continuous apoptosis of these cells by activating intrinsic and extrinsic cell death pathways to further uncouple bone formation and resorption. Interestingly, bacterial internalization appears to be required for maximal osteoblast apoptosis, and cytosolic inflammasome activation may act in concert with autocrine/paracrine death receptor-ligand signaling to induce cell death. The manipulation of apoptotic pathways in infected bone cells could be an attractive new means to limit inflammatory damage in osteomyelitis. However, the mechanism that is the most important in bacterium-induced bone loss has not yet been identified. Furthermore, it remains to be determined whether the host would be best served by preventing osteoblast cell death or by promoting apoptosis in infected cells.